2022
DOI: 10.1186/s13023-022-02491-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on Fabry Disease Patients: an examination of Mood Status, Therapy Adherence, and COVID-19 infection

Abstract: Background Fabry disease (FD) is a rare metabolic disorder, in which a lifelong enzyme replacement therapy (ERT) constitutes the cornerstone of disease-specific therapy. In this study, we examined the effects of the COVID-19 pandemic and lockdown measures on the management of FD patients. Methods We collected data in three main domains; mood status, adherence to ERT, and COVID-19 infection. We used the Hospital Anxiety and Depression Scale (HADS) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…However, in the experiences of the Fabry patients with COVID-19, severe illness and death were reported in only 2 individuals with comorbidities. 16 , 19 , 21 , 22 Karaca et al 7 reported that 5 out of 25 Fabry patients who had COVID-19 were hospitalized with major organ involvement, and 1 of them died. Our Fabry patient with COVID-19 had a mild disease in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the experiences of the Fabry patients with COVID-19, severe illness and death were reported in only 2 individuals with comorbidities. 16 , 19 , 21 , 22 Karaca et al 7 reported that 5 out of 25 Fabry patients who had COVID-19 were hospitalized with major organ involvement, and 1 of them died. Our Fabry patient with COVID-19 had a mild disease in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Of those studies, 7 were excluded to avoid redundancy, as were extracting data from the same study [29][30][31] or not showing adherence to treatment data [32][33][34][35]. Finally, 18 studies [14,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] were included in this systematic review and meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…In 8 of them [14,36,38,43,[46][47][48]50], they established the level of adherence to treatment in three ranges (low, medium, and high), with the mean prevalence in each of them being 41.4%, 30.4%, and 28.2%, respectively. On the other hand, 6 studies used the MMAS-4 [39,40,42,44,51,52]. The mean adherence reported for this type of scale was 52.9%.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations